O'Connor 50+ Club viewing a quilt made by one of their members. - Brzycki, Sharna (2014)
Various members of the O'Connor 50+ club of Witless Bay and Bay Bulls observing a quilt made by one of their members on "Craft Night", a weekly event held by the group.